Delayed Presentation of Isolated Adrenocorticotropin Insufficiency after Nivolumab Therapy for Advanced Non-small-cell lung carcinoma (NSCLC). (8th August 2018) - Shrotriya, Shiva; Rai, Manoj P; Alratroot, Ahmad; Sarzynski, Erin
Abstract : We describe a 73-year-old man who developed adrenal insufficiency 7 months after completing nivolumab therapy for advanced non-small cell lung cancer. He presented with non-specific symptoms of malaise and fatigue with an insidious 13.6 kilogram weight loss, prompting an evaluation for disease progression, which was negative. Subsequent evaluation revealed isolated adrenocorticotropin insufficiency as the aetiology, attributed to a delayed side effect of nivolumab therapy.